So, are early career researchers the harbingers of change?. Issue 3 (21st March 2019) - Nicholas, David; Watkinson, Anthony; Boukacem‐Zeghmouri, Cherifa; Rodríguez‐Bravo, Blanca; Xu, Jie; Abrizah, Abdullah; Świgoń, Marzena; Clark, David; Herman, Eti
Abstract : This article provides the final results of a 3‐year study that sought to discover whether early career researchers (ECRs) were the harbingers of change with respect to scholarly communications. Over a hundred science and social science ECRs from seven countries, spanning three continents, were depth‐interviewed annually for 3 years (2016–2018) about their attitudes and behaviours with respect to 23 scholarly issues and activities (aspects). In order to provide an accessible overarching assessment of an extremely large and complex dataset, the interview data were categorized according to the strength and direction of change exhibited and the trends and points of interest raised. Results show that all ECRs have changed in one way or another, and a small minority has changed greatly in both attitude and practice and that collaboration and research impact are the scholarly aspects where most changes have occurred, and the greatest cause of change is not so much new technology as a change of jobs.